2004
DOI: 10.1163/1568541042843531
|View full text |Cite
|
Sign up to set email alerts
|

Nematode community composition in five alpine habitats

Abstract: Soil nematodes were studied in five alpine habitats (sedge mat, pasture, peat bog, moraine, and lichen heath) in the Austrian Alps (Obergurgl, Tyrol) from 2001 to 2002. A total of 75 genera within 49 families were found. The mean nematode population density ranged from 80 to 383 individuals 100 g–1 soil and increased during the short alpine growing season. The most abundant feeding groups were bacterial feeders followed by plant-parasitic nematodes. The number of nematode taxa differed only slightly between ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
4
8
0
Order By: Relevance
“…The number of nematode genera (36) in our experimental site was less than that in alpine habitats (Hoschitz and Kaufmann, 2004) and at an intertidal marsh (Wu et al, 2005), but similar to that observed by Thornton and Matlack (2002). Nematode richness, as indicated by the number of genera (Ekschmitt et al, 2001), reflects biodiversity of soil habitat.…”
Section: Discussionsupporting
confidence: 88%
“…The number of nematode genera (36) in our experimental site was less than that in alpine habitats (Hoschitz and Kaufmann, 2004) and at an intertidal marsh (Wu et al, 2005), but similar to that observed by Thornton and Matlack (2002). Nematode richness, as indicated by the number of genera (Ekschmitt et al, 2001), reflects biodiversity of soil habitat.…”
Section: Discussionsupporting
confidence: 88%
“…The ratios of hyphal to bacterial feeding nematodes showed a constant preponderance of the bacterial feeding group. It is consistent with results of Hoschitz & Kaufmann (2004b). The minimum values of the Maturity index (MI) on the southern faces of the alpine summits were statistically signifi cant but did not seem biologically relevant (Hoschitz & Kaufmann, 2004a).…”
Section: Introductionsupporting
confidence: 88%
“…The numbers of species and genera at V3 were lower than in mountainous Carpathian meadows in Romania (Popovici & Ciobanu, 2000) and Austrian Alps (Hoschitz & Kaufmann, 2004b) but evidently greater than in Italian Alps studied by Vinciguerra (1988). Also the total SR and GR indices (Appendix 1) were lowest among the meadows studied.…”
Section: Nematode Species Compositionmentioning
confidence: 58%
See 2 more Smart Citations